Report of the Excavation of Two Cists found in making a Golf Course between Longniddry and Port Seton - Curle, Alexander O (Proceedings of the Society of Antiquaries of Scotland, 1918)
A short cist contained a crouched skeleton lying on its left side. The remains were those of an ageing adult. A long cist found nearby contained charcoal, a number of red pebbles and burnt bone identified as an adult.